What determines the finance-growth nexus? An endogenous growth model and empirical evidence - Michael Graff; Alexander Karmann (ETH Zurich, KOF Swiss Economic Institute, 2003)
An endogenous growth model on finance and growth is formulated, and empirical analyses are conducted. The model exhibits structural shifts and breaks caused by institutional changes, suggesting that a linear approach is inadequate. To address this point empirically, we fit data for 90 countries from 1960-2000 to a standard growth equation with a proxy for financial activity. Firstly, it is shown that a growth enhancing outcome of financial activity is contingent on a sound institutional framework. Then, we order the sample by control variables which follow from the model as potential causes of breaks in the adjustment process. Threshold regressions reveal non-linearities that are consistent with the model. Most importantly, we find signs for excessive financial development.
Keywords: O16; O42; O57; 330; Financial Development; Endogenous Growth; Cross-country Regressions; Institutions; Non-linearities; Finanzsektor; Entwicklung; Institutionalismus; Neue Wachstumstheorie; Schätzung; Theorie; Welt